The cartoon guide to genetics - Gonick, Larry; Wheelis, Mark. (New York : CollinsReference, 2005)
Illustrates the principles of genetics in simplified, humor-coated cartoons.
Includes bibliographical references (p. 210) and index.
Young Adult
Keywords: Genetics -- Caricatures and cartoons; Comic books, strips, etc; Genetics -- Cartoons and caricatures